PENGARUH PRODUCT PLACEMENT VOLVO DI DALAM FILM TWILIGHT SAGA: BREAKING DAWN PART 1 & PART 2 TERHADAP BRAND RECALL - Prasetya, Ghygha Yunus Widya (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
Movie scenes have become attractive means for many industries to present their products without enforced impression. Through careful designed product placement strategy, Twilight movie became the perfect promotional media for Volvo in promoting their products. Volvo is one of the premium automotive brands under the auspices of Indomobil. This well-known brand always put and positions their product merely for the target premium. Product placement is an example of a hybrid message or an attempt to influence audience at an affordable cost. Some benefits in advertising through product placement are a lot of audiences see the products so that the brand awareness and the products’ credibility would significantly increase. In conclusion, consumer’s behavior in recognizing and remembering a product might be affected by their vision, hearing, and admiration.